O uso das tecnologias de informação e comunicação na prática docente: um estudo junto aos professores dos cursos de licenciatura da Universidade Federal do Maranhão - UFMA - MOREIRA, Raphaella Abreu Carvalho Cortez (2017)
The changes that have taken place in society, especially since the end of the 1990s and in the beginning of the 21st century, with the increasing presence and the use of Information and Communication Technology (ICT) by people and students has presented new and significant possibilities of this use on the educational processes, as well as intensified the need to (re) discuss the teaching practice in the teaching levels, in specific, in the higher degree courses. In this context, the university professor must have knowledge and training that incorporates ICT in his teaching practice, since he is the professional responsible for guiding and training his students to act in the face of the complexity of contemporary society. Thus, the present research had as objective to investigate the uses of ICT by professors of undergraduate courses of the Universidade Federal do Maranhão (UFMA) in teaching practice. For this, a review of the literature was initially carried out, in order to seek theoretical basis on the theme. The main authors used were in Kenski (2012), Lévy (2010), Moran (2012), Peixoto (2009), Pimenta (2012), Sancho (2006), Tardif (2014), among others. To carry out the research, was adopted as methodological procedures a research of the exploratory-descriptive type, with method of qualitative-quantitative approach, carried out with professors of the undergraduate courses of the Campus São Luís "Cidade Universitária" of UFMA. For the collection of data, a questionnaire was formulated with open and closed questions, analyzed through statistical analysis, for closed questions, and content analysis, for the open questions, as well as discussed in the light of the theoretical reference of this research. The results of the research indicate that professors present a technological profile of knowledge and use of ICT both in social everyday, as well as in teaching. However, this knowledge was not acquired in teacher training courses and did not exploit the pedagogical potential of ICT, presenting conceptions and use restricted to its teaching practice. In general, teachers believe that the use of ICT in undergraduate courses can lead to changes in teaching, but they do not realize the importance of these to the pedagogical practice of future teachers.